THE EFFECT OF NUTRIENT IN ANODIC CHAMBER TO THE PERFORMANCE OF MICROBIAL FUEL CELL - NASHLEY URSULA MUNDI, UJAI (Universiti Malaysia Sarawak (UNIMAS), 2022)
Microbial fuel cell (MFC) is a device used to generate bioelectricity in which it converts chemical energy into electrical energy with the microorganism found in the system act as the biocatalysts. In this project, the objectives are aimed to interpret on the performance of the single-chamber microbial fuel cell with the influence of nutrients from the bamboo leaves, rice husk and coconut waste that are being oxidized by microorganisms in the anodic chamber as well as to improve the generation of electricity through microbial fuel cell by adding new nutrient contained in the organic wastes (bamboo leaves, rice husk and coconut waste) with adding potential catalyst (organic compost). There were four different experiments conducted in this project in order to understand the influence of nutrient to the performance of microbial fuel cell. In these experiments, the anode materials used are bamboo leaves, rice husk and coconut waste, in which organic compost was added to all of these mixing samples later on. The ratio between the organic wastes and organic compost were adjusted throughout conducting the experiments. The other experiment in this project is that a set of three single-chamber microbial fuel cells were connected in series and parallel to evaluate on the improvement of the bioelectricity generated. Day 5 of conducting the experiment recorded the highest current density and power density generated which are at 190.85mA/m2 and 788.58μW/m2 respectively. The single-chamber microbial fuel cells that were connected in parallel connection showed a relatively higher current density and power density at 21.47mA/m2 and 55.98μW/m2 respectively, compared to when the single-chamber microbial fuel cells were connected in series which its current density is 19.38mA/m2 with the power density at 48.75μW/m2.